Oral anticoagulant periprocedural management in patients undergoing an oral, dental implant or periodontal surgery: a prospective national observational survey - Isabelle Mahé; David Hajage; Virginie Monnet–Corti; Louis Maman; Vianney Descroix; Yann De Rycke; Loredana Radoï; Thong Nguyen; Roch Pecorari; Adeline Loing; Jonathan Ravasco; Tanguy Rouxel; et al. (Research and Practice in Thrombosis and Haemostasis)
Background: Oral surgery is a frequent invasive procedure in patients on oral anticoagulants. In usual care, the periprocedural management of these patients is questioned, with conflicting guidelines for patients on direct oral anticoagulants (DOACs). Objectives: To assess the risk of hemorrhagic and thromboembolic events during the periprocedural period (5 days before and 30 days after the oral invasive procedure). Methods: The PRatiques Anticoagulants oraux DIrects Chirurgie Orale Study (NCT 03150303) is a prospective noninterventional national study including patients receiving long-term oral anticoagulants (duration of treatment of at least 1 month) and referred to dental surgeons for an invasive procedure. Hemorrhagic and thromboembolic events and death on days 2, 7, and 30 were reported and analyzed according to anticoagulant management (interruption/continuation). Bleedings were classified according to the International Society on Thrombosis and Haemostasis classification after blinded review. Results: Overall, between July 2017 and December 2019, 523 patients (mean age 74) were recruited (345 on DOACs and 178 on vitamin K antagonists [VKAs]). During the periprocedural period, 62 events (11.8 events per 100 person-month [PM]) occurred, all local bleedings, in 50 patients (90.3% during the 7 days). The incidence of postoperative bleeding was greater in patients who continued on DOACs compared with patients who continued on VKAs (15.9/100 PM vs 5.9/100 PM; P = .003). Conversely, no significant difference was observed between patients with DOAC discontinuation and patients with VKA continuation (6.2/100 PM vs 5.9/100 PM; P = .75). Conclusion: In patients on anticoagulants undergoing an invasive oral procedure, the risk of bleeding occurs mainly within the 7 days following the procedure. Our data suggest the benefit of short perioperative discontinuation of DOACs.